Studing the Effect of Etching Process on the Ohmic Specific Contact Resistance of AlGaN/GaN HEMT - Nguyen, Trung Do; Luu, Thi Lan Anh; Le, Thi Hong Lien; Nguyen, Hoang Thoan; Nguyen, Ngoc Trung (JST: Engineering And Technology For Sustainable Development, 2021)
In electronic devices, ranging from integrated circuits to solar cells, the Ohmic specific contact resistance between metal and semiconductor is a measure of device performance. In this paper, the effect of Induction Coupled Plasma etching (ICP) on creating specific contact resistance between metals and semiconductors was investigated by linear transmission method (LTLM). The obtained results show that selecting etching depth and etch process conditions by ICP method before metal coating is a decisive step in the manufacture of low resistance Ohmic contact. The value of formed Ohmic specific contact resistance is the lowest when the etching depth ensures the metal layers to cover the doped AlGaN region at a distance of about 8nm above the AlGaN/GaN interface. With an ion power source (RIE) of 30W and a plasma power source (ICP) of 250W, the etching rate of AlGaN material is approximately 27.21 nm / minute. The Ohmic specific contact resistance of metal layers Ti (20nm) / Al (200nm) / Pd (60nm) / Au (100nm) with AlGaN semiconductor has an optimal value of ρc = 1.08 x 10-7 Ω.cm2, despite the sample was annealing at a relatively low temperature of 650°C in a nitrogen atmosphere.